The application of earned value management in event project management industry - Xin Hao, Yeoh (2014)
This thesis is aimed to study on the application of earned value management in event project management industry. Earned value management is commonly exercised to monitor and coordinate the status of a project and forecast the future performance through the presentation of cost and time. The objectives of the study are, to identify the implementation level of earned value management in event project management industry and to determine the factors that manipulating the implementation of the earned value management in event project management industry. The method being used to collect the data is through the distribution of questionnaires to the targeted respondents. Based on feedbacks from the respondents, they had agreed that the application of earned value management did enhance the project performance. The implementation level of earned value management practice in project environment is positioned in a moderate level. The future researcher is advised to carry out more study on scenario of application of earned value management in event project management industry in order to produce more supportive and adequate journals or academic articles for the study on earned value management performance of project. The diversification of earned value management application in project management could be endorsed and published if the future researcher takes initiative to conduct and carry out more related studies